Outcomes of Penetrating Keratoplasty With Imported Corneas Compared With Local Corneas. Issue 9 (September 2016) - Ababneh, Osama H.; AlOmari, Amal F.
Abstract : Purpose: The outcomes of penetrating keratoplasty (PK) were compared using local corneas obtained at the same hospital in which they were transplanted with corneas obtained from the United States and grafted at the Jordan University Hospital. Methods: A retrospective, nonrandomized review included the medical records of 484 patients who underwent PK at the Jordan University Hospital from 2007 to 2009. Patients with at least 18 months of follow-up included 71 patients in the local group and 75 patients who received imported corneas. Data regarding the preoperative vision and diagnosis, tissue characteristics, preservation-to-surgery time of donor tissue on graft survival, and postoperative outcomes were collected. Results: One hundred forty-six patients (mean age, 31.8 yrs ± 18.3 SD; range, 13–80 yrs) were included. Ninety-three (63.7%) patients were men. The most common indications for PK were keratoconus (67.8%) and corneal opacity (11%). Both groups were similar in age, indications, and outcomes. The success rates for PK after 18 months were 86% and 88% in the local and imported cornea groups, respectively; the difference between them did not reach significance ( P = 0.196). The only significant ( P < 0.001) factor was a longer preservation-to-surgery time in the imported group (8.6 ± 2.9 d) compared with the local group (4.5 ± 2.2 d). Conclusions: The success rate for PK remains relatively high (average, 87%) with both local and imported corneas. Despite the longer preservation-to-surgery time and older donor age for the imported corneas, no significant difference in graft outcomes was seen between the 2 groups.